Light Is More Important Than Nutrient Ratios of Fertilization for Cymodocea nodosa Seedling Development - Alexandre, Ana; Silva, João; Santos, Rui (Frontiers in Plant Science, 2018)
Restoration of seagrass beds through seedlings is an alternative to the transplantation of adult plants that reduces the impact over donor areas and increases the genetic variability of restored meadows. To improve the use of Cymodocea nodosa seedlings, obtained from seeds germinated in vitro, in restoration programs, we investigated the ammonium and phosphate uptake rates of seedlings, and the synergistic effects of light levels (20 and 200 µmol quanta m-2 s-1) and different nitrogen to phosphorus molar ratios (40 µM N:10 µM P, 25 µM N:25 µM P and 10 µM N:40 µM P) on the photosynthetic activity and growth of seedlings. The nutrient content of seedlings was also compared to the seed nutrient reserves to assess the relative importance of external nutrient uptake for seedling development. Eighty two percent of the seeds germinated after 48 days at a mean rate of 1.5 seeds per day. All seedlings under all treatments survived and grew during the four weeks of the experiment. Seedlings of C. nodosa acquired ammonium and phosphate from the incubation media while still attached to the seed, at rates of about twice of adult plants. The relevance of external nutrient uptake was further highlighted by the observation that seedlings’ tissues were richer in nitrogen and phosphorus than non-germinated seeds. The uptake of ammonium followed saturation kinetics with a half saturation constant of 32 µM whereas the uptake of phosphate increased linearly with nutrient concentration within the range tested (5 - 100 µM). Light was more important than the nutrient ratio of fertilization for the successful development of the young seedlings. The seedlings’ photosynthetic and growth rates were about 20% higher in the high light treatment, whereas different nitrogen to phosphorus ratios did not significantly affect growth. The photosynthetic responses of the seedlings to changes in the light level and their capacity to use external nutrient sources showed that seedlings of C. nodosa have the ability to rapidly acclimate to the surrounding light and nutrient environment while still attached to the seeds. C. nodosa seedlings experiencing fertilization under low light levels showed slightly enhanced growth if nourished with a